How Do Schools Located Near Cigarette Industries Implement the No-Smoking Policy in Schools? - A’isah Anita; Subandi Subandi; Susetyo Yuli Faj (SHS Web of Conferences)
Smoking is a behavior that is physically and psychologically harmful to humans. Smoking and the environment are two things that cannot be separated. Smoking behavior starts from adolescence and is more influenced by the environment. One environment that has special characteristics is the environment around the cigarette industry. One of the efforts of the world and the Indonesian government is to reduce smoking behavior through the school environment. The aim of this research is to analyze the smoking ban policy in schools located around the cigarette industry. Researchers used a questionnaire method to reveal demographic data and the number of smokers in schools for 446 students in 6 schools and interviews with educators, school foundations, officers who understand smoking regulations at the Health Service and Education Service, community leaders, religious leaders and teenagers. Data analysis uses thematic analysis. The result is that several themes emerge, namely the form of regulations prohibiting smoking in schools; the role of the cigarette industry in schools and society; teachers’ smoking attitudes and behavior; and kretek city culture education for students. City K apart from having many cigarette industries, there are also cultures related to cigarettes. This directly influences how schools enforce their no-smoking rules in schools.